Potenciais biomarcadores séricos de depressão e ansiedade no traumatismo cranioencefálico leve - Carlisa Silver e Silva (2022)
Cognitive, behavioral, and neuropsychiatric changes are commonly observed in patients with mild traumatic brain injury (TBI). Among psychiatric symptoms, anxiety and depression have been the most studied in this population.The purpose of this study was to investigate potential serum biomarkers associated with the development of mental health disorders, especially the occurrence of anxiety and depression, in patients with mild TBI up to one month after the trauma. In this study, patients with mild TBI were recruited from the neurology emergency department of Hospital João XXIII within 24 hours after the trauma.These patients were evaluated no later than 30 days after mild TBI through cognitive tests and self-report scales. Blood samples were also collected for biomarker analysis. Sixty-seven inflammatory, neuronal and vascular damage markers were measured in the serum of patients and controls. The study was performed with 21 patients with mild TBI (n=21) and 13 healthy controls (n=13). Patients who suffered mild TBI (n=21) had a higher incidence of anxiety and depression compared to healthy controls (n=13). There was also a difference in serum biomarkers of patients with mild TBI and participants of group control, which may suggest an association between TBI and some biomarkers as well as a connection with anxiety and depression. The identification of cognitive-behavioral and neuropsychiatric alterations and the understanding of pathophysiological factors can contribute to the development of better care and follow-up of patients with mild TBI. These findings may contribute to the development of clinical interventions.